The Relationship between the Physical Environment of the House and Family Behavior with the Incidence of Acute Respiratory Disease in Toddlers in the Koeloda Health Center - Bupu, Ferdinanda Karolina; Landi, Soleman; Ndoen, Honey Ivon (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Introduction: Acute respiratory infection (ARI) is a disease that affects the respiratory tract, including the nose, throat, and lungs. Based on data from the Ngada Regency Health Center, ARI remains a serious problem and continues to increase from 4,92% in 2020 to 5.54% in 2021. This study aimed to determine the relationship between the physical environment of the home and family behavior and the Incidence of ARI in toddlers. Method: Observational analytical research with a cross-sectional design was used. The population in this study were all toddlers in the Koeloda Health Center area, totaling 357 toddlers and the sample in this study were some of the toddlers totaling 185 toddlers. Random cluster sampling was used in this study. Data collection was conducted through interviews using research instruments in the form of questionnaires, and measurements using research instruments in the form of roll meters. This analysis uses the Chi square testResults : The results showed that there was a relationship between the type of household fuel (P=0.007), behavior of bringing toddlers to the kitchen (P= 0.002), and Incidence of ARI in toddlers. There was no relationship between room occupancy density (P = 0.078), ventilation area (P =0.235), floor type (P =0.291), and smoking behavior (P =1.000) and the incidence of ARI. Conclusion : There is a relationship between the type of household fuel and the behavior of bringing toddlers to the kitchen when cooking, and the Incidence of ARI in toddlers.